Interaction of soil enzyme activity and regeneration of Juniperus excelsa in Chaharbagh habitat of Gorgan - "Aleme Bagheri; Mahammad Matinizadeh; Yousof Torabian; Vaheid Hemmati (تحقیقات جنگل و صنوبر ایران, 2011)
Juniperus excelsa has wider distribution than other species of Juniperus in Iran. In most of habitats, different individuals have rough conditions especially in soil. One of the major problems is the lack of regeneration which can face the life and future of these habitats with challenge. The biological properties that are most useful for detecting the deterioration of soil quality are those that can be most closely related to nutrient cycles, including soil respiration, microbial biomass, nitrogen mineralization capacity and the activities of soil enzymes. In particular, enzyme activities are especially significant in soil quality assessments because of their major contribution to the soil ability to degrade organic matter. This research was carried out to study the interaction of soil enzyme activity and regeneration of Juniperus in Chaharbagh habitat in Golestan province of Iran. Sampling was done from 0-10 and 10-20 cm depths of soil under trees with and without regeneration. The activity of acid and alkaline phosphatase, dehydrogenase, urease and microbial biomass enzymes has been measured using reaction with substrate and by means of spectrophotometer. Results showed that activity of these enzymes and microbial biomass was significantly more in 0-10 cm than 10-20 cm depth because of more oxygen, suitable dispersion of roots and adequate nutrients. Existence of some microorganisms in upper depths has accelerated mineralizing nutrients. Regenerations uses these suitable nutrients. After formation of regenerations, their interaction on microorganisms have caused more permanency. This desired condition has preserved both microorganisms and regenerations.